Photonic crystals : physics and technology - Sibilia, C. (Concita) (Springer, 2008)
The aim of the work is give an overview of the activity in the field of Photonic Crystal developed in the frame of COST P11 action . The main objective of the COST P11 action was to unify and coordinate national efforts aimed at studying linear and nonlinear optical interactions with Photonic Crystals (PCs), without neglecting an important aspect related to the material research as idea and methods of realizations of 3D PC, together with the development and implementation of measurement techniques for the experimental evaluation of their potential applications in different area, as for example telecommunication with novel optical fibers, lasers, nonlinear multi-functionality, display devices, opto-electronics, sensors. The book contain contributions from authors who gave their lecture at the Cost P11 Training School. Training School was held at the Warsaw University (2007) and National Institute of Telecommunications (May 23), Warsaw. It was attended by 23 students. The focus of the School was on the work of working groups WG1 and WG3 of the COST P11 Action, concerning the active and non-linear properties of photonic crystals and the fabrication and characterisation of photonic crystal structures. This was supported by two opening lectures providing a general introduction to the topics covered within the action and a summary of the challenges faced by and achievements of the modelling and simulation activities developed during the Action.